2020
DOI: 10.26508/lsa.201900599
|View full text |Cite
|
Sign up to set email alerts
|

The health status alters the pituitary function and reproduction of mice in aCxcr2-dependent manner

Abstract: Microbiota and chronic infections can affect not only immune status, but also the overall physiology of animals. Here, we report that chronic infections dramatically modify the phenotype of Cxcr2 KO mice, impairing in particular, their reproduction ability. We show that exposure of Cxcr2 KO females to multiple types of chronic infections prevents their ability to cycle, reduces the development of the mammary gland and alters the morphology of the uterus due to an impairment of ovary function. Mammary gland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Reverse transcription was performed with 1µg of total RNA using random primers and with M−MLV enzyme (ThermoFisher, Illkirch, France). Real time quantitative PCR was performed with SYBR green Master Mix (Roche, Meylan, France), on a Light Cycler 480 instrument (Roche) as previously described [ 22 ]. Ribosomal protein S9 (rS9) and GAPDH were used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse transcription was performed with 1µg of total RNA using random primers and with M−MLV enzyme (ThermoFisher, Illkirch, France). Real time quantitative PCR was performed with SYBR green Master Mix (Roche, Meylan, France), on a Light Cycler 480 instrument (Roche) as previously described [ 22 ]. Ribosomal protein S9 (rS9) and GAPDH were used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…At steady state, CXCR2 has also been shown to be expressed mainly by neutrophils and to a lesser extent by endothelial cells [ 15 ] and is an essential regulator of neutrophil action. Previous work on CXCR2 function has shown that it was a pro-angiogenic receptor [ 16 ], but it has now been demonstrated, using Cxcr2 knock out (KO) animals, that CXCR2 is also involved in chronic obstructive pulmonary disease [ 17 ], wound healing [ 18 ], resistance to infections [ 19 ], myelin repair [ 20 ], metabolism [ 21 ] or reproduction under microbiota influence [ 22 ]. KO animals for Cxcr2 exhibit a lymphadenopathy due to an increased number of B lymphocytes and a splenomegaly owing to an accumulation of metamyelocytes and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR2 has been shown in mouse to control a variety of functions including wound healing [ 24 ], resistance to infections [ 25 ], reproduction under microbiota influence [ 26 ], senescence [ 27 ], myelin repair [ 28 ] and metabolism [ 29 ]. The potential role of CXCR2 has been described in murine preclinical models of CXCR2 gene deletion or targeting of CXCR2 protein with antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…An example of immune-pituitary interactions has been identified in a mouse mutant of the chemokine receptor, CXCR2, where null mice with chronic systemic infections were seen to exhibit impaired reproductive ability in both males and females, an effect not seen in controls [ 97 ]. Cxcr2 −/− female mice had impaired development of ovaries and mammary glands, as well as lower levels of circulating FSH, LH, PRL and GH; however, these could be rescued by transplant of organs from WT controls.…”
Section: Cytokines and Growth Factors In The Pituitary Glandmentioning
confidence: 99%